Shear induced molecular changes of exopolysaccharides from lactic acid bacteria. (December 2019) - Nachtigall, Carsten; Berger, Christiane; Kovanović, Tijana; Wefers, Daniel; Jaros, Doris; Rohm, Harald
Abstract: Exopolysaccharide (EPS) producing lactic acid bacteria are known for their positive effect on the texture of fermented dairy products, with their high water binding capacity causing changes in rheology and syneresis reduction. During manufacture, product texture is affected by shearing with an unknown impact on the properties of the EPS. By subjecting aqueous solutions of viscosity enhancing EPS from Streptococcus thermophilus DGCC7710 or dextran to defined shear treatments with a Microfluidizer, a cell disruption system or a toothed ring dispersion unit to apply different energy input, we investigated macromolecular properties and the behaviour in solution. Despite the breakage of covalent bonds, spectroscopic NMR analyses revealed that repeating unit structure remained unchanged, whereas changes in macromolecular properties such as intrinsic viscosity, hydrodynamic volume, and molecular mass strongly depended on energy input. The decrease of the dynamic viscosity of the polysaccharide solutions was significantly related to the observed decrease in molecular mass, and the impact of the EPS on technofunctional properties such as contribution to gel stiffness during acid gel formation was also affected. The results therefore indicate that mechanical energy input through shearing should be considered because product texture may be altered as a consequence of a mechanical breakdown of EPS molecules. Graphical abstract: Image 1